La influencia de la concepción franco-hispana de la Jurisprudencia en Latinoamérica - Luis Oliverio Cañarte Mantuano; Jacqueline Maria Lastenia Chiriboga Dava; José Enrique Chávez Castillo; Gladys Maria Cedeño Delgado (Iustitia Socialis, 2019)
Recibido: 23 de mayo de 2019